2007
DOI: 10.1246/bcsj.80.464
|View full text |Cite
|
Sign up to set email alerts
|

Guest-Induced Supramolecular Isomerism and Chirality of Brucine Inclusion Crystals with Aliphatic Alcohols: A Hierarchical Interpretation

Abstract: Cocrystallization of brucine with a series of aliphatic alcohols was systematically investigated to understand molecular recognition through supramolecular isomerism and chirality. Guest-induced supramolecular isomers of brucine were obtained by cocrystallization and were categorized into three structural types based on the common 2 1 helical tapelike assemblies. These supramolecular isomers were elucidated from the molecular structures on the basis of qualitative hierarchical structural analysis through supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Now our study is spreading from steroidal molecules to the surrounding natural compounds, such as brucine [128], cinchona alkaloids, and further to the surrounding organic substances, such as organic salts [129][130][131]. Supramolecular chirality of assemblies of these substances fascinates us so much.…”
Section: Discussionmentioning
confidence: 99%
“…Now our study is spreading from steroidal molecules to the surrounding natural compounds, such as brucine [128], cinchona alkaloids, and further to the surrounding organic substances, such as organic salts [129][130][131]. Supramolecular chirality of assemblies of these substances fascinates us so much.…”
Section: Discussionmentioning
confidence: 99%
“…In the motifs, molecules in front of the helical axis tilt to the right, indicating a right-handed helix. [24] 2 1 Helices of Planar Molecules…”
Section: Helices Of Bile Acids and Brucine With A Polycyclic Skeletonmentioning
confidence: 99%
“…This complementarity is often difficult to quantify, but in 1998 Rebek et al stated that the phenomena of molecular recognition in organic solutions are often optimal when the packing coefficient (pc), defined as the ratio of the van der Waals volume of the guest to the accessible volume in the cavity of the host, is equal to 55(AE9) %. [36][37][38][39][40][41][42] The van der Waals volumes of the guests 2-12 were calculated by using the method reported by Abraham et al [43] The packing coefficients were then determined and are reported in Table 1. Entries 2 and 6 ( Table 1) show that efficient complexation is observed for zwitterionic guests with very favorable pc values close to 55 % (59 and 51 %, respectively).…”
mentioning
confidence: 99%